Analysis of saprolite-hosted Rutile-Graphite deposit: a case study of Malingunde saprolite-hosted Rutile-Graphite project in Central Malawi - Zabula, Ansel Aliko (Rhodes University, Faculty of Science, Department of Geology)
The Malingunde graphite project, owned by Sovereign Metals Ltd (SML), has revealed significant potential for rutile and high-grade graphite in saprolite. This study addresses the complexity of mineral assemblages in the Malingunde area, emphasizing the coexistence of graphite and rutile. SML's exploration activities, including extensive drilling and soil sampling, have uncovered variations in associated minerals, such as muscovite, kyanite, garnets, and ilmenite. Rutile, initially discovered incidentally, has prompted further investigation, impacting the financial model of the project. This research aims to analyse the Malingunde deposit, focusing on understanding its mineralogy, formation, and potential for elements like vanadium. Geological surveys reveal the distribution of graphite in the Precambrian to lower Palaeozoic age basement complex, hosted in saprolite resulting from tropical weathering of graphitic gneisses. Exploration techniques, including remote sensing, and geophysics, are crucial in targeting graphite and rutile deposits. Ground electromagnetic surveys, airborne electromagnetic data, and GIS applications aid in identifying and quantifying mineralised areas. Geochemical analysis and metallurgical tests further contribute to understanding the ore body and processing methods. Results indicate an inverse relationship between graphite and rutile concentrations, influencing the economic viability of different regions within the project area. Correlation matrices and regression analyses reveal distinct geological conditions influencing the association of vanadium and graphite in Lifidzi and Malingunde. The study concludes with exploration potential outside the Malingunde project, highlighting regional prospects and potential byproducts like vanadium pentoxide. The ongoing metallurgical tests and pilot plant design signify the project's evolution toward production. Additionally, neighbouring licenses show potential, emphasizing the need for comprehensive research to define and quantify resources in the region. This research provides valuable insights for the mining industry, informing strategies for exploration, resource assessment, and potential byproduct utilization in similar geological settings.
Keywords: Rutile; Graphite; Saprolites; Geophysical surveys -- Malawi; Vanadium pentoxide; Geophysical surveys -- Economic aspects